Detection of quantitative trait loci for wheat (Triticum aestivum L.) heading and flowering date. (1st April 2019) - Zhao, C. H.; Sun, H.; Liu, C.; Yang, G. M.; Liu, X. J.; Wang, Y. P.; Lv, F. X.; Wu, C. Y.; Xu, J. W.; Wu, Y. Z.; Cui, F.
Abstract: Heading date (HD) and flowering date (FD) are critical for yield potential and stability, so understanding their genetic foundation is of great significance in wheat breeding. Three related recombinant inbred line populations with a common female parent were developed to identify quantitative trait loci (QTL) for HD and FD in four environments. In total, 25 putative additive QTL and 20 pairwise epistatic effect QTL were detected in four environments. The additive QTL were distributed across 17 wheat chromosomes. Of these, QHd-1A, QHd-1D, QHd-2B, QHd-3B, QHd-4A, QHd-4B and QHd-6D were major and stable QTL for HD. QFd-1A, QFd-2B, QFd-4A and QFd-4B were major and stable QTL for FD. In addition, an epistatic interaction test showed that epistasis played important roles in controlling wheat HD and FD. Genetic relationships between HD/FD and five yield-related traits (YRTs) were characterized and ten QTL clusters (C1–C10) simultaneously controlling YRTs and HD/FD were identified. The present work laid a genetic foundation for improving yield potential in wheat molecular breeding programmes.